18FDG-PET at 1-Month Intervals Is a Better Predictive Marker for GISTs That Are Difficult to Be Diagnosed Histopathologically: A Case Report. (11th October 2011) - Otsuka, Kazunori; Takahashi, Masahiro; Nanjo, Hiroshi; Miyazawa, Hideaki; Iida, Masatake; Abe, Yuki; Jin, Mario; Onishi, Hirohide; Hashimoto, Manabu; Yamamoto, Yuzo; Shibata, Hiroyuki
Abstract : Imatinib mesylate is a tyrosine kinase inhibitor of c-KIT and PDGFRA. Imatinib mesylate is an effective drug that can be used as a first-choice agent for treatment of GISTs. Prior to treatment, molecular diagnosis of c-KIT or PDGFRA is necessary; however, in some types of GISTs, it is impossible to obtain a sufficient amount of specimen for diagnosis. An inoperable or marginally resectable GIST in a 79-year-old female was difficult to be diagnosed at a molecular pathological level, and hence, exploratory treatment was initiated using imatinib combined with 18 FDG-PET evaluation at 1-month intervals. PET imaging indicated a positive response, and so we continued imatinib treatment in an NAC setting for 4 months. As a result, curative resection of the entire tumor was successfully performed with organ preservation and minimally invasive surgery. 18 FDG-PET evaluation at 1-month intervals is beneficial for GISTs that are difficult to be diagnosed histopathologically.